Russia's vision of cyberspace: a danger to regime security, public safety, and societal norms and cohesion. Issue 1 (2nd January 2019) - Pigman, Lincoln
ABSTRACT: Far from just a domain in which to counter one's enemies and a weapon to wield against them, Russian political elites view cyberspace as the source of significant threats to Russia's own national security. Since 2011, when networked protests broke out in multiple Russian cities following controversial parliamentary elections and against the backdrop of the so-called Arab Spring, Russian political elites have articulated their anxieties by constructing three major cyberthreats: that to regime security, that to public safety, and that to societal norms and cohesion. These cybersecurity narratives, the construction of which is explored in this article, are found to have dovetailed with broader national security narratives deployed by Russian political elites, reinforcing their messaging on national security issues. The article concludes with the observation that cybersecurity debates in Russia and in North American and Western European countries increasingly resemble each other, to a potentially problematic extent.